Adaptability of buildings: a critical review on the concept evolution - Askar, Rand (2021)
Our ever-evolving built environment is continuously facing emerging needs for housing, work, health, and mobility, among others. Yet, buildings are usually designed and set up as finished permanent objects, reflecting the one constant scenario in mind of defined form, function, and performance. Since change is increasingly inevitable in our life, enlarging buildings’ adaptive capacities in response to arising variables and changing conditions over their lifecycle becomes a necessity in seeking global sustainability demands. The concept of building adaptability has been a notable subject in this respect, increasingly stimulating and proposing regenerative alternatives to today’s often obsolete buildings. This paper critically reviews the existing body of knowledge on the concept of adaptability in building research. The main focus is made on the evolution of the concept interpretations and related paradigms, and on the development of its applications and strategies in the light of promoting models and trends. Drawing on the literature as a source of evidence, the paper analyzes and classifies the content of existing studies published in scientific journals and gray literature, focusing on a timeframe from 2015 up-to-date. Moreover, the paper aims to build a constructive discussion to identify potential gaps between the actual state of the art and emerging needs, which should be addressed by further research.